Intratumor heterogeneity predicts prognosis in lepidic predominant lung adenocarcinoma - Niedermaier, Benedikt Walter; Allgäuer, Michael; Muley, Thomas; Schneider, Marc; Eichhorn, Martin E.; Winter, Hauke; Klotz, Laura Valentina (Thoracic cancer, 2025)
Objective: Among the different subtypes of invasive lung adenocarcinoma, lepidic predominant adenocarcinoma (LPA) has been recognized as the lowest-risk subtype with good prognosis. The aim of this study is to provide insight into the heterogeneity within LPA tumors and to better understand the influence of other sub-histologies on survival outcome. Methods: sc dOverall, 75 consecutive patients with LPA in pathologic stage I (TNM 8th edition) who underwent resection between 2010 and 2022 were included into this retrospective, single center analysis. The proportions of different growth patterns were reported in 5% increments according to the WHO classification. Results All tumors exhibited a predominantly lepidic growth pattern (median proportion 70%, IQR 60%-85%). The invasive component included acinar (n = 66, 88%), papillary (n = 41, 55%), micropapillary (n = 14, 19%), and solid growth patterns (n = 4, 5%), with most tumors exhibiting more than one invasive growth pattern. The presence of high-risk growth, that is, micropapillary and solid, was associated with higher T stage (r = 0.423, p = 0.0002). A classification of patients as lepidic/high-risk or lepidic/low-risk based on the presence of micropapillary and solid growth patterns resulted in a significantly worse disease-free survival (p = 0.0169, 5-year DFS: lepidic/high-risk 73% vs. lepidic/low-risk: 95%) for the lepidic/high-risk group, while the groups did not differ in age, gender, smoking status, or extent of resection. Conclusion: Patients with stage I LPA exhibit considerable intratumor heterogeneity regarding growth patterns, which can be used for prognostic stratification. The occurrence of micropapillary and solid growth patterns in LPA is associated with poorer disease-free survival.